Non-Vertical Exposures to HIV, HBV and HCV Infection in Children and Adolescents-Risk of Infection, Standards of Care and Postexposure Prophylaxis - Anna Tomasik; Maria Pokorska-Śpiewak; Magdalena Marczyńska (MDPI AG, 2021)
Introduction: in the review, we aimed to present current knowledge about the risk of infection, standards of care, and postexposure prophylaxis (PEP) in pediatric patients after non-vertical exposures to HIV, HBV, and HCV infection. Materials and Methods: the latest available literature and recommendations of Centers for Disease Control and Prevention (CDC), World Health Organization (WHO), European recommendations for the management of HIV and administration of non-occupational PEP, and Polish AIDS Society were reviewed. Results: the majority of cases of non-vertical exposure to blood-borne viruses in the pediatric population consist of sexual exposition and injection with unsterilized sharp objects (usually needlestick injuries). The risk HIV, HBV, and HCV transmission depend on several factors, and each exposure should be evaluated individually with consideration of the patient's medical history. It is crucial to start antiretroviral therapy within 48 h from exposure. Treatment is continued for 28 days, and a 3-drugs regiment is recommended in the majority of cases. Decisions on hepatitis B and tetanus PEP are based on a history of vaccination. There is no PEP for hepatitis C infection, follow-up testing aims for early identification of disease and consideration of treatment options. Conclusion: all children after the non-vertical exposure to HIV, HBV, and HCV infection should be evaluated by the Infectious Disease specialist as soon as possible after the incident and qualified to post-exposure prophylaxis. Systematic diagnostic and follow-up on children after significant needlestick exposure should be maintained. Children after sexual exposure need a multidisciplinary approach. Response to reported event must be rapid and treatment must be comprehensive.